Impact of Workplace Environment Color on Worker Performance: Insights from a Cracker Factory: Dampak Warna Lingkungan Kerja terhadap Kinerja Pekerja: Wawasan dari Pabrik Kerupuk - Boy Isma Putra; Cholifah Cholifah; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to explore the influence of workplace environment color on the performance of cracker factory workers. Focusing on a Small and Medium-sized Enterprise (SME) Krupuk, the research investigates the relationship between suitable workplace colors and worker performance. The psychological impact of workplace colors on mood and task execution is examined, considering factors like emotions, concentration, and alertness. Data analysis employs SPSS software for linear regression and cross-tabulation methods, revealing that an illumination level of 44 lux leads to a completion time of 14.15 seconds in the grinding section. The study highlights the desired impact of the color yellow and underscores the significance of color selection in enhancing worker performance. Highlight: Color-Mood-Performance Link: This research examines how workplace environment color influences cracker factory workers' performance, considering psychological aspects such as mood, emotions, concentration, and alertness. Data Analysis Methods: Employing SPSS software, the study employs linear regression and cross-tabulation methods to establish connections between suitable colors, worker performance, and an illumination level of 44 lux. Yellow's Desired Impact: Results highlight the desired impact of the color yellow on worker performance, emphasizing the importance of thoughtful color selection to enhance productivity. Keyword: Workplace Environment Color, Worker Performance, Psychological Impact, Illumination Level, Color Selection